RUNX2 mutations in Taiwanese patients with cleidocranial dysplasia - Lin,Wei-De (2011)
Cleidocranial dysplasia (CCD) is an autosomal dominant human skeletal disorder comprising hypoplastic clavicles, wide cranial sutures, supernumerary teeth, short stature, and other skeletal abnormalities. It is known that mutations in the human RUNX2 gene mapped at 6p21 are responsible for CCD. We analyzed the mutation patterns of the RUNX2 gene by direct sequencing in six Taiwanese index cases with typical CCD. One of the patients was a familial case and the others were sporadic cases. Sequencing identified four mutations. Three were caused by single nucleotide substitutions, which created a nonsense (p.R391X), two were missense mutations (p.R190W, p.R225Q), and the forth was a novel mutation (c.1119delC), a one-base deletion. Real time quantitative PCR adapted to determine copy numbers of the promoter, all exons and the 3'UTR region of the RUNX2 gene detected the deletion of a single allele in a sporadic case. The results extend the spectrum of RUNX2 mutations in CCD patients and indicate that complete deletions of the RUNX2 gene should be considered in those CCD patients lacking a point mutation detected by direct sequencing.